Higher Education Integration in ASEAN: ASEAN University Network Case - Rezasyah, Teuku; Konety, Neneng; Rifawan, Affabile; Wardhana, Wahyu (JAS (Journal of ASEAN Studies), 2017)
Higher education has an important role in the region’s economic growth, with talents and   ideas developing in the process. ASEAN University Network (AUN) is the institution that facilitates cooperation among ASEAN universities and beyond. This research attempts to describe the role of AUN in enhancing regional integration in the higher education sector in ASEAN. This research uses qualitative method to get depth information and the bigger picture in the governance of AUN’s role and mechanism in regional integration of higher education system. The results of this research showed that AUN helped enhancing regional cooperation.